Elements of Bioeconomy 2019
DOI: 10.5772/intechopen.85036
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Process of Enzymatic Transformation of Biomass

Abstract: Cellulase is an enzyme which depolymerizes the cellulose into glucose. Cellulases are produced by a diverse array of microbes including fungi, bacteria, yeast and actinomycetes. Considerable research for understanding the mechanism of cellulases began in early 1950s because of the significant use of these enzymes in various industries. This review provides a general account structure and availability of lignocellulosic biomass, pretreatment strategies for effective digestion, cellulase producing organisms, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…The kinetics of polysaccharide hydrolysis are largely governed by the extent to which glycosidic bonds are exposed, which can be measured as the surface area accessible to enzymes 120 . For this reason, a pretreatment process is almost always required to remove lignin and hemicellulose to expose more of the cellulose surface and decrease its crystallinity 28,84,121 . Enzymatic depoly merization does not give degradation products and pro ceeds under mild conditions, making this method the preferred industrial process in biorefineries.…”
Section: Cellulose Depolymerization In Concentrated Acid and Ionic Li...mentioning
confidence: 99%
“…The kinetics of polysaccharide hydrolysis are largely governed by the extent to which glycosidic bonds are exposed, which can be measured as the surface area accessible to enzymes 120 . For this reason, a pretreatment process is almost always required to remove lignin and hemicellulose to expose more of the cellulose surface and decrease its crystallinity 28,84,121 . Enzymatic depoly merization does not give degradation products and pro ceeds under mild conditions, making this method the preferred industrial process in biorefineries.…”
Section: Cellulose Depolymerization In Concentrated Acid and Ionic Li...mentioning
confidence: 99%
“…Chemically pretreated pine and poplar wood [53], sawdust mixture [126], hemp [126], spruce [133], olive wastes [131], and paper mulberry wood [115] were subjected to an enzymatic hydrolysis step separate from the fermentation phase, while chemically pretreated poplar wood, pine wood [50,68], and furniture boards [114] were subjected to SSF. In the study led by Bay et al [53], the structural analyses confirmed that amorphous parts are broken down by enzymes before the crystalline parts [180][181][182]. This is due to the fact that glycosidic bonds exist within the crystalline fraction and are less reactive to hydrolysis [183].…”
Section: Enzymatic Hydrolysis Of Woody Biomass After Chemical Ptmentioning
confidence: 96%
“…Similarly, recycling of one ton of printing or copying paper saves nearly two tons of wood, [256]. The paper manufacturing industry significantly uses the lignocellulose-containing sources.…”
Section: Cellulases In Paper Manufacturing Industrymentioning
confidence: 99%
“…Bio-bleaching using enzymes is an important replacement to avoid environmental pollution. The elimination of intransigent lignin is carried out from the pulp, a process known as bleaching used to make the paper brighter and whiter paper [256]. Many paper mills globally use chlorine dioxide (ClO 2 ) as a bleaching agent for the manufacturing of top-quality white paper.…”
Section: Cellulases In Paper Manufacturing Industrymentioning
confidence: 99%
See 1 more Smart Citation